Строение пищеварительной системы корневого клеща Rhizoglyphus echinopus (Fumouze et Robin) (Acarilormes, Acaroidea) - Акимов, И.А. (Вестник зоологии, 1975)
The morphology and histology of the digestive system in adult Rhizoglyphus echinopus are described from serial sections in paraffin. The alimentary tract has a typical acarid form, characterized by a well-developed stomach bearing a posterolateral pair of the caeca, a distinct colon, postcolon and rectum. The anterior pair of the caeca is absent. The walls of the stomach, caeca, colon and postcolon consists of a single layer of cells which is enclosed by a thin non-cellular membrane and a net of muscles. The cells of the walls of the stomach with the caeca and colon may be classified in two groups.